2016
DOI: 10.1177/0361684316644838
|View full text |Cite|
|
Sign up to set email alerts
|

Still Second Class

Abstract: We surveyed 525 graduate students (61.7% females and 38.3% males) regarding their exposure to sexual and gender-based harassing events. Thirty-eight percent of female and 23.4% of male participants self-reported that they had experienced sexual harassment from faculty or staff; 57.7% of female and 38.8% of male participants reported they had experienced sexual harassment from other students. We explored the relation between sexual harassment and negative outcomes (trauma symptoms, campus safety, and institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 41 publications
2
82
0
1
Order By: Relevance
“…Despite greater experience with academia, graduate students are also not immune to being victims of harassment. A study of over 500 graduate students at a large Pacific--Northwestern public university found that 38% of female and 23% of male students reported being sexually harassed by faculty or staff (Rosenthal, Smidt, and Freyd, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Despite greater experience with academia, graduate students are also not immune to being victims of harassment. A study of over 500 graduate students at a large Pacific--Northwestern public university found that 38% of female and 23% of male students reported being sexually harassed by faculty or staff (Rosenthal, Smidt, and Freyd, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Data in this report are based on a subset of measures from a larger study that included both undergraduate and graduate student participants (see Rosenthal, Smidt, and Freyd, 2016 for graduate student findings).…”
Section: Sample 1 Methods Sample 1 Participantsmentioning
confidence: 99%
“…The general procedure of this study has been previously described in Rosenthal, Smidt, and Freyd (2016). We used Qualtrics survey software to design and distribute a survey to our randomly selected student sample.…”
Section: Procedures For Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Sexual harassment encompasses a wide range of behaviors including staring or leering; unwelcome touching; and sexual insults or taunts (Australian Human Rights Commision, 2014). Sexual harassment occurs in a range of contexts, including in the workplace (Ilies, Hauserman, Schwochau, & Stibal, 2003); educational institutions (Australian Human Rights Commision, 2017; Rosenthal, Smidt, & Freyd, 2016); public spaces (The Australia Institute, 2015) and online (Barak, 2005;Megarry, 2014).…”
Section: Sexual Harassment: Definition Prevalence and Effectsmentioning
confidence: 99%